Palestinian Experience in Stage Four Pressure Ulcer - Dartaha, Rami; Ghannam, Ghina; Jobran, Afnan Waleed (AL-Kindy College Medical Journal, 2021)
Pressure ulcer (now called Pressure injury) happens when the bony prominence like the sacrum exposes to pressure for a long period and also can cause soft tissue injury. In order to prevent and cure pressure-induced wounds, continuous and attentive repositioning is necessary. Wound management begins with the identification and aggressive management of the modifiable factors, such as positioning, incontinence, spasticity, diet, devices, and medical comorbidity, which contribute to pressure injury formation. Initial interventions include washing, cleaning, and maintaining the surfaces of the wound. In certain cases, it may be sufficient to debride the non-viable or contaminated tissue; however, operational care in more severe cases or to encourage patient satisfaction may be necessary. Our patient is a 50-year-old overweighted man, nonsmoker, and confined to a wheelchair presented with a 20*20*8 stages 4 ulcers in the sacral area after multiple failed bedside debridement. When we use the fasciocutaneous we should consider the depth of the wound and fill dead space. Here we the local situation in Palestine as those patients are usually neglected and their management is restricted to bedside debridement, with no experience in flap reconstruction operations which would dramatically improve patients’ lives. We believe that further awareness is demanded for such procedures.